The Implementation of Hazard Analysis Critical Control Points in the Amplang Production Process at UMKM X, Balikpapan - Anis Rohmana Malik; Novita Lizza Anggraini; Mayati Isabella; Adiek Astika Clara Sudarni (Universitas Islam Raden Rahmat, Malang, 2024)
Background: Amplang is a snack made primarily from fish and is usually given as souvenirs to tourists, especially in Balikpapan. The process of making amplang involves a fairly long process, that might lead to bacterial growth if not handled correctly. Therefore, Hazard Analysis and Critical Control Point is one of the methods that can be used to prevent food contamination. Purpose: The purpose of this research is to assess the Hazard Analysis and Critical Control Point implementation in the production process of amplang by Micro, Small, and Medium Enterprises of X in Balikpapan. Method: This research is qualitative in nature with a case study approach. The informants in this study were the owners and employees of Micro, Small, and Medium Enterprises of X who are responsible for the amplang production process from fish meat storage to packaging. Results and Discussion: The formulation of the Hazard Analysis and Critical Control Point stages indicates that the critical point is in the fish meat grinding process. Based on the bacterial testing results at each stage of amplang production in Micro, Small, and Medium Enterprises of X, it meets the requirements of SNI 7763:2013. Micro, Small, and Medium Enterprises of X has implemented the Hazard Analysis and Critical Control Point system effectively. To maintain and improve the existing conditions, it is recommended that the owner chooses suppliers of fresh fish raw materials who also implement food safety and personal hygiene systems. The production facility layout should be organized according to the 5R/5S principles to prevent contamination of raw materials and ensure the safety of Micro, Small, and Medium Enterprises of X workers.